Effects of the Extract of Calophyllum Inophyllum on Behavioral Indices in Rodents - Ibironke, G.F.; Ugege, O.G. (Нейрофизиология, 2015)
We examined modifications of behavioral indices evoked in rodents by introduction of an alcohol extract from leafs of Calophyllum inophyllum (С.i.) under conditions of four neurobehavioral tests. Intraperitoneal injections of 50, 100, or 200 mg/kg of the concentrated extract were used; the effects observed were compared with the action of 1 mg/kg diazepam. In the hole-board test, injections of the C.i. extract significantly suppressed the manifestations of research behavior (decreased the number of head dips into openings) in a dose-dependent manner. In the light/dark box test, considerable increases of the time of stay of mice in the dark compartment were observed after extract injections. In the open field test on mice, injections of the C.i. extract resulted in noticeable, while statistically insignificant, decreases in the general intensity of locomotion (number of crossed squares). In this test, the number of manifestations of research behavior (rearings) decreased rather considerably; the number of grooming episodes also became smaller, but suppression of this type of behavior was weaker. Testing of rats in the elevated plus-maze showed that the numbers of entries of the animals into open arms of the labyrinth significantly decreased at all doses of the extract, and the duration of stay in these arms was also smaller. Thus, the extract from the C.i. leafs containing significant amounts of biologically active compounds demonstrates rather considerable sedative effects, but these effects are combined with some anxiogenic action. The results obtained also show that anxiolythic/anxiogenic effects of a given test agent observed in different behavioral tests (considered specific from this aspect) are not fully identical and should be compared with reservations.